Estudo de viabilidade técnica de utilização em argamassas do resíduo de construção oriundo do próprio canteiro de obra - José Silva Lapa (2011)
This study evaluates physical and mechanical properties of mortars with partial and total replacement of conventional aggregate by waste (RCC) coming from a structured building in reinforced concrete and brick wall. Mortar linings of walls and ceilings were tested in compression and bond strength. Results showed that mixtures with total or partial inclusion of recycled aggregate outperformed the conventional ones used in the work. In mortar with 100% replacement of natural aggregates by recycled ones the compression resistance values increased 62.5%. In mortar made at the construction site prepared using the mill/mechanical mortarmixer, with 64.3% replacement of natural aggregates by recycled ones, the compression resistance values increased 155%. Taking the mortar with recycled aggregates which gave the best performance in previous assessments, the results obtained in pull-off tests (one value 0.29 MPa and all other values between 0.56 to 0.83 MPa) showed that it presents itself fully suitable for internal and external linings intended to receive paint or ceramic coatings and/or ornamental stones coatings.